(untitled) (Journal of Parents and Teachers, 2014)
In this article, a religion teacher exposes his experience changing his way of teaching in order to offer his students useful help. It also incorporates objectives, methodologies and a didactic unit called "The meaning of life", which was a privileged space for students to know more about themselves.